Poverty and Vulnerability in the Ethiopian Lowlands : Building a More Resilient Future - World Bank Group; U.K. Department of International Development (World Bank, Washington, DC, 2020)
This study responds to a request in March 2018 by the Ministry of Finance and Economic Cooperation (MoFEC), to the World Bank and Department for International Development (DfID) to carry out a study of the lowlands with a view to strengthening the resilience of lowland populations to external shocks. This overview synthesizes the nine self-standing chapters of the report that examine different dimensions of poverty, vulnerability, and resilience to shocks in the Ethiopian lowlands. To identify a policy agenda fostering resilience in the lowlands, the report adopts an analytical framework with three main features. First, the livelihood system of the population in the lowlands is examined in detail for the purpose of providing a better understanding of the patterns of behavior observed and the factors that are associated with the prevalence of poverty at a given point in time and changes in poverty over time. Second, a distinction is made between the poverty status of a household at a given point in time and the vulnerability of a household to poverty, which is about the likelihood of a household being poor in the future. Third, emphasis is placed on understanding the different sources of household vulnerability in the lowlands, how these sources of vulnerability have evolved over time, and how the capacity of households to cope with changes has evolved.